ANALISIS SISTEM PENGARSIPAN DATA PADA KECAMATAN LAWE BULAN MENGGUNAKAN METODE SEQUENTIAL SEARCH - Frengki Arjuna; Rismadayanti Waruwu; Anita Anita (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
In a company or organization archives play an important role in supporting the activities carried out. Archives are documents that are stored to be reused when needed, therefore if the archived documents are not done properly it will hinder the process of further activities. At the Lawe Bulan sub-district office there are problems with the archive process which is still done conventionally. This raises several obstacles, such as the document search process which takes a long time, and over time the increasing number of archive documents makes the need for hardcopy document storage greater and there will be a risk of damage or loss of documents. Based on this, the authors offer a solution using a web-based data archive system with sequential search method. Sequential search method is an algorithm used to search for random or non-sequential data by tracing the array from beginning to end. This will certainly simplify the process of searching for archival data and simplify archival activities compared to using conventional archive systems.